Outpatient versus inpatient treatment for acute pulmonary embolism - Yoo, Hugo H. B. [UNESP]; Queluz, Thais H. A. T. [UNESP]; El Dib, Regina [UNESP] (Wiley-Blackwell, 2014)
Background: Pulmonary embolism (PE) is a common life-threatening cardiovascular condition, with an incidence of 23 to 69 new cases per 100,000 people per year. Outpatient treatment instead of traditional inpatient treatment in selected non-high-risk patients with acute PE might provide several advantages, such as reduction of hospitalizations, substantial cost saving and an improvement in health-related quality of life. Objectives: To compare the efficacy and safety of outpatient versus inpatient treatment for acute PE for the outcomes of all-cause and PE-related mortality; bleeding; and adverse events such as hemodynamic instability, recurrence of PE and patients'satisfaction.Search methodsThe Cochrane Peripheral Vascular Diseases Group Trials Search Co-ordinator (TSC) searched the Specialised Register (last searched October 2014) and the Cochrane Central Register of Controlled Trials (CENTRAL; 2014, Issue 9). The TSC also searched clinical trials databases. The review authors searched LILACS (last searched November 2014). Selection criteria: Randomized controlled trials of outpatient versus inpatient treatment in people diagnosed with acute PE. Data collection and analysis: Two review authors selected relevant trials, assessed methodological quality, and extracted and analyzed data. Main results: We included one study, involving 339 participants. We ranked the quality of the evidence as very low due to not blinding the outcome assessors, the small number of events with imprecision in the confidential interval (CI), the small sample size and it was not possible to verify publication bias. For all outcomes, the CIs were wide and included clinically significant treatment effects in both directions: short-term mortality (30 days) (RR 0.33, 95% CI 0.01 to 7.98, P = 0.49), long-term mortality (90 days) (RR 0.98, 95% CI 0.06 to 15.58, P = 0.99), major bleeding at 14 days (RR 4.91, 95% CI 0.24 to 101.57, P = 0.30) and 90 days (RR 6.88, 95% CI 0.36 to 134.14, P = 0.20), recurrent PE within 90 days (RR 2.95, 95% CI 0.12 to 71.85, P = 0.51) and participant satisfaction (RR 0.97, 95% CI 0.92 to 1.03, P = 0.30). PE-related mortality, minor bleeding, and adverse course such as hemodynamic instability and compliance were not assessed by the single included study. Authors' conclusions: Current very low quality evidence from one published randomized controlled trial did not provide sufficient evidence to assess the efficacy and safety of outpatient versus inpatient treatment for acute PE in overall mortality, bleeding and recurrence of PE adequately. Further well-conducted research is required before informed practice decisions can be made.